Tubularized Incised Plate Urethroplasty Using Buccal Mucosa Graft for Repair of Penile Hypospadias - Tavakkoli Tabassi, Kamyar; Mohammadi Rana, Toktam (Urology Journal, 2012)
PURPOSE: To describe the results of penile hypospadias repair using the Snodgrass method with buccal mucosa graft (BMG), supported by double dartos flap as a second layer. MATERIALS AND METHODS: In a prospective cohort study, 21 consecutive patients underwent hypospadias repair using the Snodgrass method and BMG as the urethral plate, with the addition of double dartos flap for covering the neourethra. Patients were followed up, and outcomes and complications were recorded. RESULTS: The mean age of the patients was 6.57 ± 3.69 years (range, 2 to 15 years) and the mean follow-up period was 8.42 ± 2.19 months (range, 6 to 12 months). The following minor complications, not requiring additional intervention, were recorded: 2 subjects developed slight chordee < 30 degrees; 2 developed wound infection; and 1 had meatal stenosis postoperatively. Only one patient required additional surgical intervention resulting in a success rate of 95%. No urethrocutaneous fistula occurred in our subjects. CONCLUSION: Fortifying a combination of BMG and Snodgrass method with double dartos flap decreases the rate of complication in hypospadias repair significantly.